The Effectiveness of Student Team Achievement Division Method with Gitmind in the Teaching Writing for Junior High School Students - Ratna Nurlia; Wiratno Wiratno (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Writing is one of the language skills that middle school students need to have. The purpose of this study was to determine the effectiveness of using the Student Group Performance Method with Gitmind to improve the writing ability of 7th grade students at Junior High School. In this study, a quasi-experimental design was used. The sample includes two classes (groups), an experimental class of 25 students and a control class of 24 students. This study uses the ANCOVA formula to analyze data. Research shows that instructional students who use Gitmind and the Student Team Performance Division method have better academic results. It is supported by the estimated marginal mean for the two groups, which is 56. 963 for the grammar translation method and 78. 474 for students taught using the Student Group Achievement Division with Gitmind method.